Sustainable and smart cities: A review - Dos Santos, Maria José Palma Lampreia (2019)
This paper addresses the main challenges to be overcome so that cities in the future can be sustainable and also smart cities in the African Continent. The main goal of the paper is to analyses the main constraints to urban development in the African Continent in order for these cities to became smart cities in the future. The methodology was based on a literature revision of all the papers referred in Social Science Citation Index and SCOPUS Elsevier from Q2 to Q1. The results confirm the existence of huge challenges, problems and restrictions on social, economics, environmental and political issues in Africa and also confirm that smart cities will only be possible in Africa when the current problems of sustainable development (economic, social, environmental and political) are overcome. However, the paper allows us to understand why, this is the first paper in the literature to address the topic of smart cities in Africa. It should be noted that in this continent there are at least two of the world's largest cities in terms of inhabitants and the growth of population rate of the African continent is about 2.5%. This is a global problem to handle. The concern about the problems of sustainable development in this region and how to promote it towards sustainable cities concerns everyone and the next steps will affect all of the world’s sustainable development.